2012
DOI: 10.3892/ijmm.2012.1186
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment of therapeutic cells with poly(ADP-ribose) polymerase inhibitor enhances their efficacy in an in vitro model of cell-based therapy in myocardial infarct

Abstract: The potential of cell-based therapies in diseases involving ischemia-reperfusion is greatly hampered by the excessive loss of administered cells in the harsh and oxidative environment where these cells are supposed to act. Therefore, we investigated if inhibition of poly(ADP-ribose) polymerase (PARP) in the therapeutically added cells would lead to their increased viability and, subsequently, to an enhanced effect in an in vitro simulated ischemia-reperfusion (I-R) setting. Ischemic conditions were simulated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…So, for example, pre-treatment with 30–1000 nM PJ34 significantly protected neurons from cell death induced by oxygen and glucose deprivation in a dose-dependent manner [21] . PJ34 (10 or 100 µM) also protected cardiomyoblast cells against H 2 O 2 -induced injury [39] . In human umbilical vein endothelial cell culture, Mathews and Berk [40] showed that PJ34 at 10 µM reduced H 2 O 2 -induced cell death.…”
Section: Discussionmentioning
confidence: 95%
“…So, for example, pre-treatment with 30–1000 nM PJ34 significantly protected neurons from cell death induced by oxygen and glucose deprivation in a dose-dependent manner [21] . PJ34 (10 or 100 µM) also protected cardiomyoblast cells against H 2 O 2 -induced injury [39] . In human umbilical vein endothelial cell culture, Mathews and Berk [40] showed that PJ34 at 10 µM reduced H 2 O 2 -induced cell death.…”
Section: Discussionmentioning
confidence: 95%
“…For this reason, we have set the length of simulated ischemia to a level where only 5–20% of cells survived without any treatment, which reflects the conditions found at the site of the injury in the heart after myocardial infarction. We demonstrated the suitability of this model by detecting significantly elevated levels of oxidative stress and cellular necrosis after the simulation of ischemia-reperfusion in our earlier publication [42]. The effects were analyzed at 24 hours because we wanted to rule out the potential differentiation of the added stem cells, which occurs over longer time periods.…”
Section: Discussionmentioning
confidence: 99%
“…Ischemia-reperfusion was simulated in vitro by oxygen and glucose deprivation as described previously in our earlier publications [4042]. Briefly, 30.000/well H9c2 cells in 12-well plates were incubated in glucose-free DMEM in an atmosphere of 0.5% O 2 and 99.5% N 2 for 160 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…However, persistent excessive activation of PARylation promotes depletion of NAD + and ATP, leading to further cell death [31]. PJ34 is a highly effective PARP inhibitor, and its inhibition of PARP-1 activity is mainly through the competitive blocking of NAD + binding sites on the PARP-1 molecule [32,33].…”
Section: Parp-1 Inhibitor Reduces Gsdmd Defect-mediatedmentioning
confidence: 99%